POWER, CENTRALITY AND EMBEDDEDNESS AS MECHANISMS TO INCREASE SUBSIDIARIES’ EFFICIENCY IN GRASPING KNOWLEDGE ON THEIR LOCAL NETWORKS - Isaac, Victor Ragazzi; Barcelos, Eduardo Jorge Branco Vieira; Ogasavara, Mario Henrique (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
The International Business literature emphasizes interorganizational relationships in business networks, based on embeddedness, as a mechanism for multinational enterprises to improve their performance. However, an in-depth analysis of the literature shows that embeddedness alone is insufficient to subsidiaries to gain local competitive advantage. Thus, in order to better understand this issue, a systematic review of the literature was carried out using the online database with 45 articles that address three central constructs in networks embeddedness, power and centrality. The analysis suggests a gap in the studies on power and centrality of the subsidiary in its external network. Therefore, through a conceptual model, but with managerial application, this article suggests that the subsidiary use embeddedness, power and centrality in an integrated way to optimize access to the tangible and intangible resources, and reduce network conflicts needed to obtain specific (SSA) and global competitive advantage (FSA).